Analysis of an interleaved zero‐voltage switching/zero current switching resonant converter with duty cycle control. Issue 2 (1st February 2013) - Lin, Bor‐Ren; Cheng, Po‐Jen
Abstract : An interleaved series resonant converter with fixed frequency pulse‐width modulation (PWM) is presented to achieve load current sharing, ripple current cancelation, zero‐voltage switching (ZVS) for power switches and zero‐current switching (ZCS) for rectifier diodes. Two three‐level DC converters with clamped diodes and flying capacitor are adopted to share load current. The voltage stress of power switches is clamped at one‐half of DC bus voltage. The interleaved PWM scheme is used to control two converters in order to reduce the output current ripple and size of output capacitor. The series resonant tank in three‐level PWM converter is adopted to realise ZVS turn‐on for all power switches andZCS for rectifier diodes. Thus, the switching losses of active switches are reduced and the reverse recovery losses of rectifier diodes are eliminated. The fixed frequency PWM operation is adopted to regulate output voltage, so that the drawback of a wide range of switching frequency in the conventional series resonant converters is overcome. Finally, experiments based on a scale‐down prototype are provided to verify the effectiveness of the proposed converter.